From niche to necessity: a decade of building health economics for better patient access to innovative medicines in Malaysia / June Choon Wai Yee - Choon, June Wai Yee (Faculty of Pharmacy, 2024)
When I first co-chaired the Health Economics Forum back in 2013 at Monash University, few people had even heard of health economics. It was a niche area, and its relevance to healthcare policy was not widely understood. The first edition of the Pharmacoeconomics Guidelines in Malaysia had only been published in 2012 by the Pharmaceutical Services Programme, Ministry of Health (MOH). It was an important starting point aimed at promoting local research and embedding pharmacoeconomics into policy decisions.